Nova Jaguaribara: representações sobre o modo de vida urbano - Braz, Milena Marcintha Alves (2005)
This work results from a field research undertaken in Nova (New) Jaguaribara, a city designed and built by the state government of Ceará as an alternative to resettle the displaced population of Jaguaribara (a historic city with a large rural zone) due to the construction of The Castanhão Dam. This investigation sought to understand the representations of residents about the way of life in the planned city. This is because the new model has brought new forms of sociability, different from what the residents were accustomed. Given the above, the intention was to understand how the lifestyle of the residents has changed under the new urban configuration. To describe and analyze this problem, I gathered qualitative data collected through semi-structured interviews, recorded with local residents, informal conversations andobservations recorded in field journal. Also researched official documents of state government on the Dam project and the newcity as well as newspaper clippings on the subject. We can find in the reports analyzed the views of respondents about the planned city, ranging from praise to the large and modern structure, to dissatisfaction about having to live with "outsiders" that move around the city. Other respondents referred to problems such as: neighborhood, survival, urban sanitation, aesthetics and spatial distance.